Macrofouler Community Succession in South Harbor, Manila Bay, Luzon Island, Philippines during the Northeast Monsoon Season of 2017?2018. - Trinidad, C.B.
Manila Bay is one of the most important bodies of water in the Philippines. Within it is the Port of Manila South Harbor, which receives international vessels that could carry non-indigenous macrofouling species. This study describes the species composition of the macrofouling community in South Harbor, Manila Bay during the northeast monsoon season. Nine fouler collectors designed by the North Pacific Marine Sciences Organization (PICES) were submerged in each of five sampling points in Manila Bay on 06 Oct 2017. Three collection plates from each of the five sites were retrieved every four weeks until 06 Feb 2018. Identification was done via morphological and CO1 gene analysis. A total of 18,830 organisms were classified into 17 families. For the first two months, Amphibalanus amphitrite was the most abundant taxon; in succeeding months, polychaetes became the most abundant. This shift in abundance was attributed to intraspecific competition within barnacles and the recruitment of polychaetes. Diversity and richness values increased across all sites, which are commonly observed in primary succession events, while evenness values were low due to the dominance of Amphibalanus amphitrite and polychaetes. New macrofouling species in Manila Bay were reported: Barbatia foliata, Membranipora sp., a stylochid flatworm, a venerid clam, and hesionid, phyllodocid, and cirratulid polychaetes. More importantly, non-indigenous species were observed: Mytilopsis sp., Mytella charruana, Brachidontes pharaonis, Hydroides elegans, and the North Pacific giant flatworm Kaburakia excelsa. These species are potentially invasive and may alter the ecosystem of Manila Bay. Thus, it is recommended to further monitor the seasonally variable macrofouling community of South Harbor to observe annual succession patterns and to use DNA barcoding techniques more extensively for identification of macrofoulers ? especially the polychaete taxa ? to the species level and rapid early detection of potentially invasive species.
Keywords: Science -- Periodicals; Biological invasion; DNA barcoding; Species abundance; Fouling; Species diversity